Refractory composition, and processing method of back-filling fire prevention section penetration part
The refractory composition, with a specific blend of organic and inorganic components, addresses the challenges of processability and stability in fire-resistant materials by ensuring excellent handling and maintaining shape integrity after heating and combustion.
Patent Information
- Application Number
- JP2023159231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-22
AI Technical Summary
Existing fire-resistant compositions face issues with processability due to drying out over time, and they become brittle and prone to collapse after heating and combustion, making them difficult to maintain filling properties.
A refractory composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water reducing agent, with specific mass proportions to ensure excellent processability, storage stability, and shape stability after heating and combustion.
The refractory composition maintains excellent processability and shape stability after storage and exposure to high temperatures, effectively addressing the brittleness and collapse issues of previous compositions.
Smart Images

Figure 2025050435000001 
Figure 2025050435000002 
Figure 2025050435000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fire-resistant composition and a method for backfilling a fire compartment penetration. [Background technology]
[0002] 2. Description of the Related Art It is known to provide fireproofing to walls, floors, etc. of buildings by coating or filling them with a fireproof material (fireproof composition). As such a fireproof material, a putty-like fireproof material containing water, an inorganic filler, a thickener, and a binder is used (see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-050118 Summary of the Invention [Problem to be solved by the invention]
[0004] The technology of Patent Document 1 had the problem that even if a plastic film was used for packaging, if the water evaporated over time, the fireproof putty would dry out and become hard, making it difficult to process. Furthermore, the technology of Patent Document 1 has a problem in that the filled refractory material becomes brittle and crumbles easily after heating and combustion, making it difficult to maintain its filling properties.
[0005] The present invention has been made in view of the above circumstances, and provides a refractory composition which has excellent processability, relatively good processability even after storage, and excellent shape stability after heating and combustion. [Means for solving the problem]
[0006] According to the present invention, there is provided a fire-resistant composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent, wherein the proportions of each component when the total of the three components, the organic compound-based binder material, the inorganic compound, and the organic compound-based water-reducing agent, is taken as 100 mass%, are 0.5 to 20.0 mass% of the organic compound-based binder material, 60.0 to 98.5 mass% of the inorganic compound, and 0.1 to 20.0 mass% of the organic compound-based water-reducing agent.
[0007] As a result of extensive investigations, the present inventors have found that a fire-resistant composition containing the above-mentioned components in the above-mentioned ratios can solve the above problems, leading to the completion of the present invention.
[0008] [1] A fire-resistant composition comprising an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent, wherein the proportions of each component when the total of the three components, i.e., the organic compound-based binder material, the inorganic compound, and the organic compound-based water-reducing agent, is taken as 100% by mass, are 0.5 to 20.0% by mass of the organic compound-based binder material, 60.0 to 98.5% by mass of the inorganic compound, and 0.1 to 20.0% by mass of the organic compound-based water-reducing agent. [2] The fire-resistant composition according to [1], wherein the organic compound-based binder material includes a compound containing a sodium salt. [3] The fire-resistant composition according to [1] or [2], wherein the organic compound-based water-reducing agent comprises a compound containing a sodium salt. [4] The fire-resistant composition according to any one of [1] to [3], wherein the inorganic compound includes a phosphoric acid-based compound. [5] The fire-resistant composition according to any one of [1] to [4], wherein the organic compound-based binder material contains a compound containing a sodium salt, the inorganic compound contains a phosphate-based compound, and the organic compound-based water-reducing agent contains a compound containing a sodium salt. [6] The fire-resistant composition according to any one of [1] to [5], wherein water is contained in an amount of 10 to 70 mass% based on 100 mass% of the fire-resistant composition. [7] A method for backfilling a fire compartment penetration, comprising a construction step of using the fireproof composition according to any one of [1] to [6]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] 1. Composition of the fireproof composition The fire-resistant composition of the present invention contains an organic compound-based binder material, an inorganic compound, and an organic compound-based water-reducing agent. The fire-resistant composition of the present invention is a composition that is excellent in processability and can be used as a putty that can be deformed to fit a shape. That is, the composition can be provided as a putty-like fire-resistant composition.
[0010] <Organic compound binder materials> The organic compound-based binder material is a material that acts as a binding agent to bind the individual components of the fire-resistant composition together.
[0011] The organic compound-based binder material is a binding agent made of an organic compound, and by mixing an appropriate amount, the fireproof composition can be made into a putty-like composition with a hardness suitable for application. The organic compound-based binder material may be used alone or in combination of two or more kinds. The organic compound-based binder material preferably contains a compound containing a sodium salt.
[0012] The organic compound-based binder material is preferably a hydrophilic polymer. Examples of hydrophilic polymers include water-soluble polymers that are soluble in water and water-absorbent polymers that can absorb water and expand, and specific examples of such polymers include starch, cellulose compounds, polyvinyl alcohol, modified acrylic acid ester copolymers, polyethylene oxide, polypropylene oxide, ethylene oxide-propylene oxide copolymers, ethylene oxide-propylene oxide-phenyl glycidyl ether copolymers, ethylene oxide-propylene oxide-allyl glycidyl ether copolymers, and sodium alginate.
[0013] Examples of the cellulose-based compounds include methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and derivatives thereof such as salts thereof. Examples of the salt of carboxymethylcellulose include sodium carboxymethylcellulose and ammonium carboxymethylcellulose.
[0014] The modified acrylic acid ester copolymers include a crosslinked product of sulfoethyl acrylate-acrylamide-acrylic acid copolymer sodium salt and a crosslinked product of an acrylic acid polymer partially formed with a sodium salt.
[0015] When the total of the organic compound-based binder material, the inorganic compound, and the organic compound-based water reducing agent (hereinafter referred to as "three components") is 100 mass%, the ratio of the organic compound-based binder material is 0.5 to 20.0 mass%, preferably 0.7 to 14.0 mass%, and more preferably 1.1 to 8.0 mass%. If the ratio of the organic compound-based binder material is too small, the fireproof composition may be too soft, resulting in insufficient processability or workability. If the ratio of the organic compound-based binder material is too large, the fireproof composition may be too hard, resulting in insufficient processability. The ratio of the organic compound binder material when the total of the above three components is 100 mass % is, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0 mass%, and may be within a range between any two of the numerical values exemplified here.
[0016] <Inorganic compounds> The shape of the inorganic compound may be, for example, a sphere, an elliptical sphere, a cube, a rectangular parallelepiped, or a random shape, and may be hollow or solid. The average particle size of the particulate inorganic compound is, for example, 10 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and even more preferably 40 to 200 μm. The "average particle size" refers to the particle size at an integrated value of 50% in the particle size distribution determined by a laser diffraction / scattering method. These may be used alone or in combination of two or more.
[0017] Examples of inorganic compounds include metal oxides such as alumina, silica, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; glass beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon balloons, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, perlite, obsidian, perlite, rosin, diatomaceous earth, dehydrated sludge, boron, sodium tetraborate hydrate (borax), and phosphate compounds. These may be used alone or in combination of two or more. From the viewpoint of shape stability after combustion, the inorganic compound preferably contains aluminum hydroxide or a phosphoric acid compound, and more preferably contains aluminum hydroxide and a phosphoric acid compound.
[0018] <Phosphate compounds> The phosphoric acid compounds include, in addition to phosphoric acid compounds, phosphorous acid compounds, hypophosphorous acid compounds, metaphosphoric acid compounds, pyrophosphoric acid compounds, and polyphosphoric acid compounds.
[0019] Examples of phosphate compounds include aluminum monophosphate, sodium monophosphate, potassium monophosphate, calcium monophosphate, zinc monophosphate, aluminum diphosphate, sodium diphosphate, potassium diphosphate, calcium diphosphate, zinc diphosphate, aluminum triphosphate, sodium triphosphate, potassium triphosphate, calcium triphosphate, zinc triphosphate, magnesium triphosphate, ammonium monophosphate, ammonium diphosphate, tricalcium phosphate, aluminum phosphate, etc.
[0020] Examples of the phosphite compounds include aluminum phosphite, aluminum hydrogen phosphite, sodium phosphite, potassium phosphite, calcium phosphite, and zinc phosphite.
[0021] Examples of hypophosphite compounds include aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, and zinc hypophosphite.
[0022] Examples of metaphosphate compounds include aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, zinc metaphosphate, and sodium hexametaphosphate.
[0023] An example of the pyrophosphate compound is sodium pyrophosphate.
[0024] Examples of the polyphosphate-based compound include ammonium polyphosphate and melamine-modified ammonium polyphosphate.
[0025] The ratio of the inorganic compound when the total of the above three components is 100% by mass is 60.0 to 98.5% by mass, preferably 84.5 to 98.3% by mass, and more preferably 90.5 to 97.9% by mass. If the ratio of the inorganic compound is too small, the shape stability after heating and burning may be insufficient. If the ratio of the inorganic compound is too large, the processability may be poor. The ratio of the inorganic compound when the total of the above three components is 100% by mass is specifically, for example, 60.0, 61.0, 62.0, 63.0, 64.0, 65.0, 66.0, 67.0, 68.0, 69.0, 70.0, 71.0, 72.0, 73.0, 74.0, 75.0, 76.0, 77.0, 78.0, 79.0, 80. 0, 81.0, 82.0, 83.0, 84.0, 84.5, 85.0, 86.0, 87.0, 88.0, 89.0, 90.0, 90.5, 91.0, 92.0, 93.0, 94.0, 95.0, 96.0, 97.0, 97.9, 98.0, 98.3, 98.5 mass%, and may be within a range between any two of the numerical values exemplified here. and may be within a range between any two of the numerical values exemplified here.
[0026] From the viewpoint of shape stability after heating and combustion, the phosphoric acid compound is preferably aluminum hydrogen phosphite, ammonium polyphosphate, or the like.
[0027] <Organic compound water reducing agent> The organic compound-based water reducing agent is a compound made of an organic compound, and is a dispersing agent that has the effect of dispersing other components. The dispersing effect is obtained, for example, by the repulsion of static electricity. Examples of the organic compound-based water reducing agent include lignin-based compounds, naphthalenesulfonic acid-based compounds, aminosulfonic acid-based compounds, polycarboxylic acid-based compounds, polyether-based compounds, etc. These may be used alone or in combination of two or more.
[0028] Examples of lignin compounds include metal salts of lignin sulfonate such as magnesium salt of lignin sulfonate, sodium salt of lignin sulfonate, and calcium salt of lignin sulfonate, as well as modified products thereof.
[0029] Examples of naphthalenesulfonic acid compounds include sodium naphthalenesulfonate-formaldehyde condensate, sodium naphthalenesulfonate-formaldehyde condensate, and the like.
[0030] Examples of the polyether compounds include carboxyl group-containing polyether compounds such as methacrylic acid-methacrylic acid ethylene oxide ester copolymer salts.
[0031] When the total of the above three components is taken as 100% by mass, the ratio of the organic compound-based water reducing agent is 0.1 to 20.0% by mass, preferably 0.3 to 14.0% by mass, and more preferably 0.7 to 8.0% by mass. If the ratio of the organic compound-based water reducing agent is too small, the workability after storage may be insufficient. If the ratio of the organic compound-based water reducing agent is too large, the workability, workability, and strength after drying may be poor. Specifically, the ratio of the organic compound-based water reducing agent when the total of the above three components is taken as 100% by mass is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9. 0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0 mass%, and may be within a range between any two of the numerical values exemplified here.
[0032] The organic compound-based water reducing agent preferably contains a compound containing a sodium salt. Preferred organic compound-based water reducing agents include sodium lignin sulfonate, sodium naphthalenesulfonate-formaldehyde condensate, sodium naphthalenesulfonate-formaldehyde condensate, and the like, which have a sodium salt in their skeletons.
[0033] In addition, additives such as thermally expandable compounds, fibrous compounds, AE (Air Entraining) agents, preservatives, antifungal agents, antioxidants, softeners, and tackifiers may be appropriately added to the fire-resistant composition to the extent that the physical properties are not impaired.
[0034] <Thermally expandable compound> The thermally expandable compound is not particularly limited as long as it expands when heated, and examples thereof include microspheres, melamine, azo compounds, nitroso compounds, hydrazine derivatives, bicarbonates, vermiculite, kaolin, mica, thermally expandable graphite, etc. Among these, it is preferable to include thermally expandable graphite from the viewpoint of thermal expansion.
[0035] <Thermal expandable graphite> Thermally expandable graphite is a crystalline compound that is obtained by surface-treating graphite powder such as natural graphite or pyrolytic graphite with an inorganic acid such as sulfuric acid or nitric acid, and a strong oxidizing agent such as concentrated nitric acid or permanganate, and that maintains a graphite layer structure. When exposed to a temperature equal to or higher than the expansion start temperature (about 200°C) under normal pressure, it thermally expands by 100 times or more. The graphite powder such as natural graphite or pyrolytic graphite may be deoxidized or further neutralized.
[0036] The proportion of the thermally expandable graphite is preferably 0.3 to 30.0 parts by mass when the total of the above three components is 100 parts by mass. By being in this range, both the thermal expandability and the shape stability after thermal expansion can be achieved.
[0037] <Fibrous compounds> Fibrous compounds include inorganic fibrous compounds and organic fibrous compounds, and may contain both inorganic fibrous compounds and organic fibrous compounds. The fibrous compound only needs to have a fibrous shape. Examples of the cross-sectional shape of the fibrous compound include circular, elliptical, polygonal, etc. The ratio L / D of the length L to the diameter D of the fibrous compound is, for example, greater than 10, preferably 50 or more, and more preferably 100 or more. The upper limit of L / D is not particularly defined, but is, for example, 10,000. The diameter D of the fibrous compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The length L of the fibrous compound is, for example, 0.05 to 10 mm, preferably 0.1 to 8 mm, and more preferably 0.2 to 5 mm.
[0038] Examples of the inorganic fibrous compound include glass fiber (E glass fiber, C glass fiber, S glass fiber, D glass fiber), rock wool, ceramic fiber (silica alumina fiber, alumina fiber, silica fiber), zirconia fiber, carbon fiber, bulk alkali earth silicate fiber, gypsum fiber, carbon fiber, metal fiber, slag fiber, basalt fiber, etc.
[0039] Examples of the organic fibrous compound include meta-aramid fiber, para-aramid fiber, amide fiber, pulp fiber, cellulose fiber, polyparaphenylene benzobisoxazole fiber, polyarylate fiber, etc.
[0040] <AE agent> Examples of the AE agent include anionic surfactants, nonionic surfactants, resin acid salt surfactants, etc. These may be used alone or in combination of two or more.
[0041] The fireproof composition of the present invention preferably contains water from the viewpoint of facilitating the work of sealing gaps between pipes and cables and fire walls in buildings. When the fireproof composition contains water, the proportion of solids is preferably 30 to 90 mass%, more preferably 50 to 70 mass%. The fireproof composition contains preferably 10 to 70 mass%, more preferably 30 to 50 mass% of water in 100 mass% of the fireproof composition. If the proportion of water is small (the solid content is high), the putty may become crumbly and may be difficult to process. If the proportion of water is large (the solid content is low), the putty may become too soft and may be difficult to process and work. The water content may be, for example, 10, 15, 20, 25, 26, 30, 35, 40, 45, 50, 55, 60, 65, or 70% by mass, or may be within a range between any two of the values exemplified here.
[0042] The fire-resistant composition of the present invention can be used as a joint material for sealing gaps between pipes and cables and fire walls in buildings.
[0043] 2. Method for producing fire-resistant composition The fire-resistant composition of the present invention can be produced by mixing and stirring the above three components, additives as required, and water using a mixer or the like.
[0044] 3. Backfilling method for fire compartment penetrations A method for backfilling a penetration into a fire compartment according to another aspect of the present invention is a method having a construction step of using the above-mentioned fireproof composition.
[0045] In the construction process, for example, the fireproof composition is filled into gaps between a fire wall or the like serving as a fire compartment through which pipes and cables in a building penetrate, and the pipes and cables themselves. EXAMPLES
[0046] 1. Preparation of the Refractory Composition The components shown in Tables 1 to 4 were mixed and stirred using a mixer according to the compositions (units: mass%) in the tables to prepare putty-like fireproof compositions of the Examples and Comparative Examples. Note that in the tables, the amounts of the binder material, inorganic compound, water-reducing agent, and medium in relation to a total of 100 mass% (total composition) are shown for the total of the three components of the binder material, inorganic compound, and water-reducing agent, and for the medium, and further the amounts of the binder material, inorganic compound, and water-reducing agent in relation to a total of 100 mass% of the above three components are shown.
[0047] [Table 1] [Table 2] [Table 3] [Table 4]
[0048] Details of the components in the table are as follows: <Organic compound binder materials> Sodium carboxymethylcellulose: "Sodium carboxymethylcellulose" manufactured by Hayashi Pure Chemical Industries, Ltd. Ammonium carboxymethylcellulose: "Kiccholate NA-H" manufactured by Nichirin Chemical Industry Co., Ltd. Acrylic acid polymer partial sodium salt: Fujifilm Wako Pure Chemical Industries, Ltd. "Super absorbent polymer (acrylate salt type)" Methylcellulose: Shin-Etsu Chemical Co., Ltd. "MCE-4000" <Inorganic compound binder materials> Bentonite: "Akagi" manufactured by Hojun Co., Ltd.
[0049] <Inorganic compounds> Aluminum hydroxide: "C-301N" manufactured by Sumitomo Chemical Co., Ltd. Aluminum hydrogen phosphite: "NSF" manufactured by Taihei Chemical Industry Co., Ltd. Ammonium polyphosphate: HP-APP II, manufactured by SCM Industrial Chemical Co., Ltd.
[0050] <Organic compound water reducing agent> - Sodium lignosulfonate: "Pearlex NP" manufactured by Nippon Paper Industries Co., Ltd. Magnesium lignosulfonate: "Sunex P321" manufactured by Nippon Paper Industries Co., Ltd. Naphthalenesulfonic acid formalin condensate sodium: "Mighty HS" manufactured by Kao Corporation Naphthalenesulfonic acid-formaldehyde condensate sodium salt: Kao Corporation's "Mighty 150" Carboxyl-containing polyether compound: Kao Corporation's "Mighty 1000M" <Inorganic compound water reducing agent> Sodium tripolyphosphate: Manufactured by Yoneyama Chemical Industry Co., Ltd.
[0051] <Various evaluations> The fire-resistant compositions of the Examples and Comparative Examples were subjected to various evaluations as shown below. The results are shown in Tables 1 to 4.
[0052] <Workability> The fireproof compositions of the Examples and Comparative Examples before drying (before storage over time as described below) were measured for softness (softness A) in accordance with JIS A5752 at a load of 150 g and a temperature of 21°C. The measurement was performed by vertically penetrating a specified cone into the test piece, and the penetration depth was measured to the nearest 0.1 mm. Then, the workability was evaluated according to the following evaluation criteria based on the penetration depth. [Evaluation Criteria] ◎: The penetration depth is 180 [1 / 10 mm] or more but less than 220 [1 / 10 mm]. ○: Penetration depth is 150 [1 / 10 mm] or more and less than 180 [1 / 10 mm]; Or, it is greater than or equal to 220 [1 / 10 mm] and less than 250 [1 / 10 mm]. △: Penetration depth is 110 [1 / 10 mm] or more and less than 150 [1 / 10 mm]; Or, it is greater than or equal to 250 [1 / 10 mm] and less than 280 [1 / 10 mm]. ×: The penetration depth is less than 110 [1 / 10 mm] or 280 [1 / 10 mm] or more.
[0053] <Workability after storage over time (workability over time)> The fireproof compositions (before storage) before drying of the examples and comparative examples were put into 80 μm-thick polyethylene bags, sealed, and stored at 40° C. for 90 days to obtain fireproof compositions (after storage). The fireproof compositions (after storage) thus obtained were measured for softness (softness B) at a load of 150 g and a temperature of 21° C. in accordance with JIS A5752. The measurement was performed by vertically penetrating a specified cone into the test piece, and the penetration depth was measured to the nearest 0.1 mm. Then, based on the penetration depth, the processability after storage over time was evaluated according to the following evaluation criteria. [Evaluation Criteria] ◎: The penetration depth is 150 [1 / 10 mm] or more. ○: The penetration depth is 130 [1 / 10 mm] or more and less than 150 [1 / 10 mm]. △: The penetration depth is 90 [1 / 10 mm] or more and less than 130 [1 / 10 mm]. ×: The penetration depth is less than 90 [1 / 10 mm] or 280 [1 / 10 mm] or more.
[0054] <Softness change rate> The rate of change in softness is the rate of change in softness before and after storage, and is a value calculated based on the following formula. Softness change rate (%) = 100 x (softness A - softness B) / softness A [Evaluation Criteria] ◎: Less than 25%. ○: 25% or more and less than 30%. △: 30% or more and less than 50%. ×: 50% or more.
[0055] <Workability (non-stickiness to gloves)> A latex glove was put on and 100 g of the undried fire-resistant composition (before the above-mentioned storage) of each of the Examples and Comparative Examples was gripped 10 times, after which the weight of the deposit on the glove was measured and the weight of the deposit was calculated based on the following formula. Then, based on the weight of the deposit, the non-stickiness of the glove was evaluated according to the following criteria. Weight of the deposit [g] = (weight of the glove after squeezing the fire-resistant composition 10 times) - (weight of the original glove) [Evaluation Criteria] ⊚: The weight of the attached matter is less than 0.1 g. ◯: The weight of the deposit is 0.1 g or more and less than 0.4 g. △: The weight of the attached matter is 0.4 [g] or more and less than 0.7 [g]. ×: The weight of the attached matter is 0.7 g or more.
[0056] <Strength after drying> Using the fireproof composition before drying of the examples and comparative examples (before the above-mentioned storage over time), a test piece of 30 mm long x 30 mm wide x 4 mm thick was prepared, and this was dried under the condition of 110 ° C. for 24 hours to obtain a test piece of the fireproof composition after drying. The test piece was broken at a compression speed of 50 mm / min using a three-point bending test jig (upper pushing side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm) and the strength (three-point bending fracture strength) was measured. Here, the higher the three-point bending fracture strength, the higher the shape stability after drying. Then, based on the three-point bending fracture strength, the shape stability after drying was judged according to the following evaluation criteria. [Evaluation Criteria] ◎: Three-point bending breaking strength is 60 [N] or more. ○: The three-point bending breaking strength is 50 [N] or more and less than 60 [N]. △: The three-point bending breaking strength is 40 [N] or more and less than 50 [N]. ×: The three-point bending breaking strength is less than 40 [N].
[0057] <Shape stability after heating and burning> Using the fireproof composition before drying of the examples and comparative examples (before the above-mentioned storage over time), a test piece of 30 mm long x 30 mm wide x 4 mm thick was prepared, and this was dried under the condition of 110 ° C. for 24 hours to obtain a test piece of the fireproof composition after drying. After leaving the dried test piece in an atmosphere maintained at 300 ° C. for 0.5 hours, a three-point bending test jig (upper pushing side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm) was used to measure the strength (three-point bending fracture strength) when the test piece was broken under the condition of a compression speed of 50 mm / min. Here, the higher the three-point bending fracture strength, the higher the strength after heating and burning. Then, based on the three-point bending fracture strength, the shape stability after heating and burning was judged according to the following evaluation criteria. [Evaluation Criteria] ⊚: Three-point bending breaking strength is 2.0 [N] or more. ◯: The three-point bending breaking strength is 1.5 [N] or more and less than 2.0 [N]. △: The three-point bending breaking strength is 1.0 [N] or more and less than 1.5 [N]. ×: The three-point bending breaking strength is less than 1.0 [N].
Claims
1. An organic compound-based binder material; An inorganic compound; An organic compound-based water reducing agent, The ratio of each component when the total of the three components, the organic compound-based binder material, the inorganic compound, and the organic compound-based water reducing agent, is 100 mass %: 0.5 to 20.0% by mass of the organic compound-based binder material, 60.0 to 98.5% by mass of the inorganic compound, 0.1 to 20.0 mass% of the organic compound-based water reducing agent, The fire-resistant composition according to claim 1,
2. The fire-resistant composition of claim 1 , wherein the organic compound-based binder material comprises a compound containing a sodium salt.
3. The fire-resistant composition according to claim 1 or 2, wherein the organic compound-based water-reducing agent comprises a compound containing a sodium salt.
4. The fire-resistant composition according to claim 1 or 2, wherein the inorganic compound comprises a phosphoric acid-based compound.
5. the organic compound-based binder material includes a compound containing a sodium salt, The inorganic compound includes a phosphoric acid compound, The fire resistant composition of claim 1 , wherein the organic compound-based water reducer comprises a compound containing a sodium salt.
6. The fire-resistant composition according to claim 1 or claim 2, wherein the fire-resistant composition contains 10 to 70 mass% of water in 100 mass% of the fire-resistant composition.
7. A method for backfilling a fire compartment penetration, comprising a step of applying the fireproof composition according to claim 1 or 2.
Citation Information
Patent Citations
Refraction composition
JP2001058878A
Alumina cement composition, and monolithic refractory obtained by using the composition
JP2003119067A
Silicon carbide material for monolithic refractory excellent in driability and monolithic refractory material
JP2003321276A
Carbon-containing castable refractory and method for producing carbon-containing castable refractory
JP2018184315A
Refractory material, refractory material stored in container, and construction method of refractory material
JP2021050118A